2012
DOI: 10.1007/s00128-012-0548-4
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Responses and Recovery Patterns in the Liver of Oreochromis niloticus Exposed to Chlorpyrifos-Ethyl

Abstract: Chlorpyrifos is the most common insecticide in freshwater ecosystems, and detected in agricultural and fishery product. In this study, Oreochromis niloticus were exposed to 5, 10 and 15 ppb sublethal concentrations of chlorpyrifos in order to determine the oxidative stress response in liver. Acetylcholinesterase (AChE) activity was significantly inhibited. Superoxide dismutase activity (SOD) increased after 15 days of chlorpyrifos treatments at all concentrations (146.95%, 53.04%, 208.70%, respectively). Malon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Significant interaction effects between chlorpyrifos and vitamin E were observed for 12 dipeptides. Collectively, these findings are in agreement with published studies demonstrating chlorpyrifos induces oxidative stress in multiple model systems [36,37,38,39,40]. Alpha tocopherol supplementation at the studied concentration did not counteract these effects, suggesting that vitamin E, except its ability to partially restore dipeptide levels, has a relatively limited ability to rescue chlorpyrifos-induced oxidative stress in salmon hepatocytes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Significant interaction effects between chlorpyrifos and vitamin E were observed for 12 dipeptides. Collectively, these findings are in agreement with published studies demonstrating chlorpyrifos induces oxidative stress in multiple model systems [36,37,38,39,40]. Alpha tocopherol supplementation at the studied concentration did not counteract these effects, suggesting that vitamin E, except its ability to partially restore dipeptide levels, has a relatively limited ability to rescue chlorpyrifos-induced oxidative stress in salmon hepatocytes.…”
Section: Discussionsupporting
confidence: 91%
“…No effect of vitamin E supplementation was however seen on PDK2 transcription in the cells. CuZn superoxide dismutase (SOD1) and catalase (CAT), suggested markers for longer-term chlorpyrifos exposure (15 days) in the Nile tilapia ( Oreochromis niloticus ) by Oruc [36], were not among the affected transcripts in cultured Atlantic salmon hepatocytes. To see effects on typical oxidative stress response genes, fish studies suggest that longer-term chlorpyrifos exposure is needed [37].…”
Section: Discussionmentioning
confidence: 99%
“…The fish were randomly stocked in five groups (2 aquaria/group, duplicates) where the SP free diet was fed to the control group while the second group was fed the basal diet supplemented with 1% SP (HerbaForce, Lewes, UK) without CPF (48%, El Nasr chemical Co., Abu-Rawash, Egypt) exposure. Additionally, CPF (15 µg/L) was added as indicated by Oruc [23] to water and fish were fed the basal diet supplemented with SP at 0, 0.5, and 1% (third, fourth, and fifth groups, respectively). The glass aquaria were siphoned daily to remove the feces and remaining diets and refilled with CPF mixed water.…”
Section: Fish Diet Chlorpyrifos (Cpf) and Experimental Designmentioning
confidence: 99%
“…Bantu et al () reported an increase in SOD activity in liver of Labeo rohita after 15 days of exposure to chlorantraniliprole. Similarly, chlorpyrifos exposure also caused significant increases in SOD activity in liver tissues of Oreochromis niloticus (Oruc, ).…”
Section: Discussionmentioning
confidence: 99%